On the taxonomic position of Panicum scabridum (Poaceae, Panicoideae, Paspaleae) - Scataglini, María Amalia (2014)
Panicum scabridum, an incertae sedis species of Panicum s.l., is here included in the genus Coleataenia, following a phylogenetic analysis based on one new ndhF sequence of the species and associated morphological data. Panicum scabridum and species of Coleataenia are cespitose and perennial plants, with a lower glume (1-)3-5-nerved, 1/3 to 3/4 of the spikelet, upper glume and lower lemma 5-9-nerved, and upper anthecium smooth, shiny, and indurate. Within Coleataenia, P. scabridum appeared as the sister taxon of the species pair C. prionitis and C. petersonii; these three species are the only NADP-me taxa of tribe Paspaleae exhibiting two bundle sheaths around the vascular bundles, i.e., with an outer parenchymatous sheath and an inner mestome sheath with specialized chloroplasts. The new combination Coleataenia scabrida is proposed and a lectotype is designated.